PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN SIMPAN PINJAM PADA KOPERASI PEGAWAI REPUBLIK INDONESIA UNIVERSITAS NEGERI PADANG (KPRI-UNP) BERBASIS WEB DAN SMS GATEWAY - Adris Faizal; Zulhendra Zulhendra; Elfi Tasrif (Universitas Negeri Padang, 2014)
Designing of management information systems at KPRI UNP savings and purpose to generate a savings and loan system design and web -based SMS gateway multiuser and provide services in the process of membership management, management of deposits, loan management and capital management. To achieve the goal of this application using a programming language Java2 Enterprise Edition ( J2EE ), Java2 Standard Edition ( J2SE ), and the MySQL database authentication level configuration in the form of a username and password. To provide data and information security MD 5 and session is used in password. With the savings and loan management information systems and web based SMS gateway can provide ease of certain stakeholder to perform data processing deposits loan data, the data search process and facilitate the process to generate the report. The information distribution’s process of saving and loand management information sistem on KPRI UNP can be accessed online and through SMS media. In addition, database is used as data storage so it can be accessed easily. Keywords : Savings and loan management system, web, SMS gateway, Java2 Enterprise Edition ( J2EE ).